Avaliação do efeito probiótico de Bifidobacterium longum 51A em modelo murino e de cultura celular de lesões inflamatórias cutâneas - Yasmin Chalfoun Pomárico de Souza (2017)
Probiotics have many beneficial effects beyond intestinal health, including over clinical and aesthetic cutaneous aspects. Despite there are many studies in the area, the action mechanisms by which these beneficial effects are performed are not completely elucidated yet. In this study, we aimed to evaluate the probiotic potential of Bifidobacterium longum 51A (BL51A) over inflammatory cutaneous aspects in a murine model of hairless mice and in an organ culture model. We assessed immunomodulatory effects of BL51A on its active state, in hairless mice, with inflammation induction by oxazolone topical administration, performing evaluation of transepidermal water loss (TWEL), enzymatic assays of eosinophil peroxidase (EPO) and myeloperoxidase (MPO). Higher EPO activity was observed on sensibilized mice, indicating tecidual eosinophilia on sensibilized mice. This tecidual eosinophilia caused by oxazolone was reduced, in a significative way, by oral administration of BL51A probiotic, showing its immunomodulatory effect over this parameter. On histological analysis of eyelid human skin, there was a small inflammatory reaction caused by Substance P, and BL51A lysate caused an increase in perivascular cells in the dermis, which were correlated to immunohistochemistry results, indicating anti-inflammatory function, with negative correlation to IL-1β and TNF-α and positive correlation to IFN-γ and IL-10, showing this citokyne’s importance on cutaneous homeostasis. Our data suggest a probiotic capacity of BL51A lysate over cutaneous health, by immunomodulation, which needs validation on future studies.